O modelo de halos e o espectro de potência da matéria escura morna - Martins, Jéssica Silvano [UNESP] (2015)
In this work we review the formalism of the Halo Model, and its applications. In the Halo Model all the matter of the universe is contained in virialized dark matter halos, as a result of gravitational collapse. The distribution of dark matter within these halos, and how they are distributed in the universe are the main features to caracterize them. We'll show the theory that describes the Halo Model and test is efficiency by comparing it to numerical simulations of structure formation in the universe, using the power spectrum. We'll also do an adaptation of Halo model to warm dark matter, and show how this type of matter supress the structure formation of the universe in small scales